Object Tracking with the Drone: Systems Analysis - Abbas Aqeel Kareem; Dalal Abdulmohsin Hammood; Ruaa Ali Khamees; Nurulisma Binti Hj. Ismail (Journal of Techniques)
The fast improvement in computer vision and the increase in the range of its application around the world. And at the same time the improvement of unmanned aerial vehicles (UAV). The computer vision application is being integrated with the drone to achieve several purposes. one computer vision application that is used with the drone is object tracking. This type of task is used with the drone to achieve semi-autonomous movement of the drones, depending on the movement of the pre-determined target. This work categorizes the two methods to design object tracking by drone.